2013
DOI: 10.2105/ajph.2013.301485
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Associated With Screening for Traumatic Brain Injury Among US Veterans Seeking Homeless Services

Abstract: We identified the prevalence of traumatic brain injury (TBI) among homeless veterans and assessed the TBI-4, a screening tool created to identify TBI history. Between May 2010 and October 2011, 800 US veterans from two hospitals, one eastern (n = 122) and one western (n = 678) completed some or all measures. Findings suggested that 47% of veterans seeking homeless services had a probable history of TBI (data for prevalence obtained only at the western hospital). However, psychometric results from the screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 7 publications
(3 reference statements)
2
20
0
Order By: Relevance
“…The increased number of referrals for clients with complex co-morbidities that affect performance in daily life, such as TBI, was similar to other studies [2]. A major difference in findings of this study is that there does not seem to be role confusion as was reported in a study of perception of occupational therapy by nurses on an inpatient mental health unit [40]. While beyond the scope of the study, this may be influenced by the realities of integrated primary care, where client challenges in executing activities of daily living are routinely demonstrated to team members and the role of occupational therapy is more easily understood, in comparison to an inpatient setting where high acuity and active symptoms of psychosis may restrict the type of real-life interventions and lead to some role confusion.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The increased number of referrals for clients with complex co-morbidities that affect performance in daily life, such as TBI, was similar to other studies [2]. A major difference in findings of this study is that there does not seem to be role confusion as was reported in a study of perception of occupational therapy by nurses on an inpatient mental health unit [40]. While beyond the scope of the study, this may be influenced by the realities of integrated primary care, where client challenges in executing activities of daily living are routinely demonstrated to team members and the role of occupational therapy is more easily understood, in comparison to an inpatient setting where high acuity and active symptoms of psychosis may restrict the type of real-life interventions and lead to some role confusion.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, there is increased awareness in those serving homeless persons that TBI specifically is very common and complicates successful housing and other goals. However, there are limited studies addressing the more complex client that is homeless with TBI [4,[28][29][30][31][32][33][34]40].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated here, the BISQ not only meets these minimal requirements but is also relatively brief, easy to administer in a wide range of settings and populations, has good construct validity and criterion validity, 40,43,68,69 and appears to be more sensitive to comprehensive TBI history than many existing measures. 56,57,59,87 The BISQ is not without limitations, and other tools may be more appropriate in some settings. A report on a subset of results of large-scale expansion of the initial BISQ validation study 63 is currently under review.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies suggest that single-item questions about TBI history miss more than 35% of the individuals found to have sustained a TBI via a subsequent structured interview. 56,57 Carefully worded single-item queries can of course provide valuable data in large-scale health outcomes studies designed to evaluate the association of TBI with other health issues or behaviors but do not suffice for estimating TBI prevalence.…”
Section: Methods For Tbi Screeningmentioning
confidence: 99%